Reflections on the reinvestment of gains from real estate capital gains and their taxation under IRS: constitutional (dis)conformities with the requirements of Decree-Law. 57/2024, of 10 September and Law 56/2023, of 6 October - PICA, Luís Manuel (Revista Jurídica Portucalense, 2025)
The article analyses the regime for the reinvestment of real estate capital gains under IRS, with a special focus on the changes introduced by Decree-Law 57/2024, of 10 September, and its constitutional compliance. The new requirement that the property sold must have been formally allocated as a tax residence in the 12 months prior to its sale raises questions about legal certainty and the protection of taxpayers' trust. The study points out that the taxation of real estate capital gains is anchored in the principle of ability to pay, requiring that only income realised be taxed. However, the new rule may constitute inauthentic retroactivity, as it affects legal situations constituted under the previous legal regime and may frustrate the legitimate expectations of taxpayers who were counting on the exclusion from taxation of these manifestations of wealth.